A 0.18-μm CMOS voltage-to-frequency converter with low circuit sensitivity - Koay, Kuan Chuang (2019)
A process, voltage, and temperature insensitive resistor-to-frequency converter is proposed. This insensitivity is achieved by matching the current-defining capacitor in a novel switched-capacitor (SC) voltage-to-current (V-I) converter with the integrating capacitor in a conventional relaxation oscillator. Implemented in 0.18-μm CMOS technology, the SC V-I converter together with the relaxation oscillator and voltage regulator occupies 0.45 mm 2 . This paper has shown a sensitivity of 199.9 Hz/(μQ/Q), which is based on a center frequency of 125 kHz. Testing with a commercial sensor, the sensor interface has demonstrated a sensitivity of 1.269 kHz/psi. The sensor interface consumes only 112.5 μW at 1.5-V power supply. Therefore, it is suitable for Internet-of-Things applications.